Viability of probiotic (Bifidobacterium, Lactobacillus acidophilus and Lactobacillus casei) and nonprobiotic microflora in Argentinian Fresco cheese - Vinderola, Celso Gabriel (2000)
We evaluated the suitability of Argentinian Fresco cheese as a food carrier of probiotic cultures. We used cultures of Bifidobacterium bifidum (two strains), Bifidobacterium longum (two strains), Bifidobacterium sp. (one strain), Lactobacillus acidophilus (two strains), and Lactobacillus casei (two strains) in different combinations, as probiotic adjuncts. Probiotic, lactic starter (Lactococcus lactis and Streptococcus thermophilus), and contaminant (coliforms, yeasts, and molds) organisms were counted at 0, 30, and 60 d of refrigerated storage. Furthermore, the acid resistance of probiotic and starter bacteria was determined from hydrochloric solutions (pH 2 and 3) of Fresco cheese. The results showed that nine different combinations of bifidobacteria and L. acidophilus had a satisfactory viability (count decreases in 60 d <1 log order) in the cheese. Both combinations of bifidobacteria and L. casei cultures assayed also showed a satisfactory survival (counts decreased <1 log order for bifidobacteria but no decrease was detected for L. casei). On the other hand, the three combinations of bifidobacteria, L. acidophilus, and L. casei tested adapted well to the Fresco cheese environment. When a cheese homogenate at pH 3 was used to partially simulate the acidic conditions in the stomach, the probiotic cultures had an excellent ability to remain viable up to 3 h. At pH 2, the cell viability was more affected; B. bifidum was the most resistant organism. This study showed that the Argentinian Fresco cheese could be used as an adequate carrier of probiotic bacteria.